THE INFLUENCE OF KOREAN POP CULTURE TOWARD CONSUMER INTENTION ON SELECTING KOREAN FOODS - Wicaksono, Liswindwinanto; La Are, Robert (Emerging Markets : Business and Management Studies Journal, 2016)
The purpose of the research is to find out the influence of Korean Pop Culture toward consumerintention on selecting Korean food. Korean Drama and Korean pop music are two phenomenal Korean pop culture which are spreaded around the world. In 1997, Korean Drama was first broadcast in China, following with the big step in 2004 where Korean Drama exported also to Hong Kong and Taiwan while Korean Pop Music start to gain popularity in the late of 1990s. In Indonesia, Korean Drama and K-pop music began to be popular in beginning of 2000?s. Their popularity are followed by Korean foods in 2014. This research is to look specifically on whether Korean Pop Culture influence Indonesian people to choose Korean foods as their options. Using SPSS software and with simple linear regression method analysis, 100 respondents? data collected is processed through validity and reliability test, classical assumption test and hypothesis testing. The results show that Korean Pop Culture influence Indonesian people to choose Korean foods.